2017
DOI: 10.1002/ceat.201600579
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of Canola Oil to Biodiesel Using CaO/Talc Nanopowder as a Mixed Oxide Catalyst

Abstract: A series of heterogeneous catalysts including different molar ratios of CaO/talc was synthesized to study the transesterification reaction of canola oil and methanol under different reaction conditions. Characterization and kinetic results revealed that the activity of this catalyst was enhanced due to the increase of CaO/talc molar ratio value leading to an improvement in the biodiesel production. Moreover, the effect of various parameters on the activity of the undertaken catalysts was studied in order to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…1, which indicated that the ILs had a strong acidity. At the same concentration, the acidity decreased in the following order: sulfuric acid > [C 3 [27]. The cationic structures of the ILs also had a noteworthy influence on their acidity because the anion was the same.…”
Section: Acidity Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…1, which indicated that the ILs had a strong acidity. At the same concentration, the acidity decreased in the following order: sulfuric acid > [C 3 [27]. The cationic structures of the ILs also had a noteworthy influence on their acidity because the anion was the same.…”
Section: Acidity Analysismentioning
confidence: 98%
“…Heterogeneous catalyst processes are environmentally benign and offer the possibility of recycling and reusing the catalysts. But the required reaction conditions are rigor, such as needing higher reaction temperature, and most heterogeneous catalysts are not degradable, which would also impact the environment [3]. Lipase-catalyzed processes have many advantages, but the enzymatic inactivation, low yield of fatty acid methyl esters, long reaction time, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, this research team focused on heterogeneous catalysts' development by using clays. In this case, biodiesel production of CaO/Talc, (Maleki et al, 2017) and K 2 CO 3 /Talc (Salmasi et al, 2020) catalysts, (with FAME yield of 96.7% and 98.4%) from the transesterification reaction of canola and sunflower oils was published.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, biodiesel is a mixture of methyl esters with longchain fatty acids and is typically generated from nontoxic and biological resources. Transesterification of vegetable oils is the most common method to produce biodiesel [1][2][3][4]. Various vegetable oils such as from soybean [5], palm [6], sunflower [7], canola [8], and babassu [9] have been used to produce biodiesel by transesterification reaction.…”
Section: Introductionmentioning
confidence: 99%